Characterization of Retinal Nerve Fiber Layer Thickness in a Cohort with Glutamic Acid Decarboxylase 65 and Glycine Receptor Autoimmunity. (5th December 2022) - Hoshina, Yoji; Wong, Ka-Ho; Galli, Jonathan; Greenlee, John; Klein, Julia; Soldan, M. Paz; Clardy, Stacey; Fjeldstad, Anette; Rose, John; Kadish, Robert
Abstract : Objective: To describe the retinal nerve fiber layer (RNFL) with the demographic and clinical profile in patients with glutamic acid decarboxylase 65 (GAD65) and glycine receptor (GlyR) neurological autoimmunity. Background: GAD65 and GlyR autoimmunity can cause a wide range of clinical phenomena, including stiff-person spectrum disorder (SPSD) and epilepsy. Both GAD65, through γ-aminobutyric acid-ergic neurons, and GlyR interact in the retina. Optical coherence tomography (OCT) has previously been used in a variety of neurological disorders to establish baseline characteristics and monitor disease course. This presents a noninvasive opportunity to evaluate for a biomarker that may assist with the treatment of these rare but debilitating disorders. Design/Methods: OCT measures of RNFL by sectors were studied in patients with GAD65 and GlyR neurological autoimmunity and compared to that of 148 healthy control eyes. Patients' baseline characteristics were also reviewed retrospectively from medical records. Results: Of the 14 patients included in this study, 12 patients were female, and the mean age was 52.6 ± 16.8 (22-79) years when OCT was performed. Ten had GAD65 autoimmunity and 4 had GlyR autoimmunity. Patients with GAD or GlyR autoimmunity showed lower RNFL thickness in multiple sectors compared to the healthy control group. This result was most apparent in the anti-GAD65 antibody subgroup. Eleven patients had SPSD, one patient had epilepsy, and two had non-specific symptoms. Conclusions: This study provides insight into baseline RNFL thickness in a group with GAD65 and GlyR autoimmunity, two conditions that may produce varied symptoms. While limited by sample size, RNFL thinning was seen in the GAD65 and GlyR autoimmunity groups, and it was most evident in the anti-GAD65 subgroup. This provides a baseline characterization and suggests that future studies should be conducted to determine the utility of OCT as a biomarker for these conditions.